Association of PTPN22-C1858T Polymorphism With Susceptibility to Mycobacterium tuberculosis and Mycobacterium leprae Infection: A Meta-Analysis - Li, Shuping; Wang, Xiaohua; Zhao, Yuming; Yang, Juan; Cui, Tianjiao; Zhao, Zhizhuang Joe; Chen, Yun; Zheng, Zhihua (Frontiers in Immunology, 2021)
Abstract It was previously published that single-nucleotide polymorphism rs2476601 (PTPN22 [protein tyrosine phosphatase non-receptor type 22]-C1858T) might be related to increased sensibility to Mycobacterium tuberculosis and M. leprae infection. However, the results were inconclusive despite a high degree of similarity between both parameters. Herein, we carried out this meta-analysis to systematically summarize and articulate the correlation between PTPN22-C1858T polymorphism and mycobacterial infection. The susceptibility of PTPN22-C1858T carriers with autoimmune conditions receiving immunosuppressive therapy to M. tuberculosis and M. leprae infection was determined. A systematic retrieval of studies on relevance of PTPN22-C1858T polymorphism to susceptibility of M. tuberculosis or M. leprae infection was performed in Chinese National Knowledge Infrastructure, PubMed and Embase databases. We regarded Odds ratios (ORs) and 95 % confidence intervals (CIs) as the determined effect size. Finally, four and two case-control studies on tuberculosis and leprosy, respectively, were included. In all genetic models, without indicated association between PTPN22-C1858T polymorphism and tuberculosis’s susceptibility. [C versus T: OR = 0.22 (95 % CI: 0.09–0.50, PH = 0.887); CT versus CC: OR = 0.21 (95 % CI: 0.09–0.49, PH = 0.889); TT+CT versus CC: OR = 0.21 (95 % CI: 0.09–0.49, PH = 0.889)]. A significantly increased risk of leprosy was perceived in patients with the PTPN22-C1858T polymorphism [C versus T: OR = 2.82 (95 % CI: 1.02–7.81, PH = 0.108)]. While the PTPN22-C1858T polymorphism is irrelevant to higher susceptibility to the infection of M. tuberculosis in Caucasians and Asians, it is relevant to increased susceptibility to the infection of M. leprae. However, the results of M. leprae are supposed to interpreted with prudence owing to the limited quantity of studies and heterogeneity. Further well-designed studies with sufficient populations are required to verify our conclusions.